Physicochemical And Emulsifying Properties Of Pre-Treated Octenyl Succinic Anhydride (Osa) Sago Starch In Emulsion - Saw, Sue San (2021)
Sago starch is abundant in Malaysia and it has the potential to be used as an emulsifier. However, native starch is generally hydrophilic and there is a need to increase its hydrophobicity by modification in order to increase its ability to stabilize emulsion. Therefore, this research was designed to increase the hydrophobicity as well as effectiveness of sago starch as an emulsifier. In this study, sago starch was pre-treated with heat moisture treatment (HMT) (single pre-treatment), STARGEN enzyme (single pre-treatment), and heat moisture treatment followed by STARGEN enzyme (dual pre-treatment) prior to octenyl succinic anhydride (OSA) modification. Enzyme-treated OSA (EN OSA) showed the highest degree of substitution (DS) (0.0152) followed by heat moisture-enzyme-treated OSA (HMT EN OSA) (0.0119) and heat moisture-treated OSA (HMT OSA) (0.0105). SEM micrograph revealed rough surface with their edges lose some definition for all OSA modified starches. Among all samples, EN OSA showed the smallest particle size, where the particle size of EN OSA had reduced from 31 μm to 28 μm. The ability of all pre-treated OSA sago starches to stabilize emulsion was then investigated. Compared to other starches, EN OSA had significantly highest emulsifying activity and produced a thick viscous emulsion layer after emulsification. After 56th days (8th week) of storage at room temperature, EN OSA showed the highest stability by exhibiting the highest emulsion index which is between 0.37 (starch concentration 200 mg / mL) to 0.56 (starch concentration 500 mg/mL).